(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The subject of the strategic vision is of great importance to all companies because they live in an environment of rapid change in various areas of life. Supports the performance of its operations better, towards choosing the appropriate strategy and achieving success. The research aims to determine the level of interest of the researched company in the research variables (strategic vision and strategic choice). As for the research method, it was relied on the descriptive analytical approach, the method of personal interviews and the use of the questionnaire as a means to obtain data from the sample of (136) people who are at the job level (department manager, assistant department manager, branch manager, assistant branch manager) in the insurance company And through the results achieved, the research proved that the strength of the impact of the components of the strategic vision on the strategic choice is of a high amount, and based on this, the components of the strategic vision The strategic vision derives its importance from the strength of its influence on the strategic choice,The research reached to work on deepening the link between the components of the strategic vision and ensuring the quality of the provided insurance services and trying to take advantage of this link in formulating the company’s future plans in the field of quality assurance and improvement, making the required changes and choosing the best alternative, and the need to invest the influence relationship between the strategic vision and the strategic choice. And taking into account the dimensions mentioned in the research, because it has a role in achieving the company’s future goals.